MAFG-DT promotes prostate cancer bone metastasis through activation of the Wnt/β-catenin pathway - Wang, Chongwen; Zhou, Zheng; Ye, Yongjie; Zhou, Liqiang; Wang, Jialun; Zhang, Zhi (Frontiers in Oncology, 2024)
BackgroundProstate cancer (PCa) ranks as the second leading cause of cancer-related mortality among men. Long non-coding RNAs (lncRNAs) are known to play a regulatory role in the development of various human cancers. LncRNA MAFG-divergent transcript (MAFG-DT) was reported to play a crucial role in tumor progression of multiple human cancers, such as pancreatic cancer, colorectal cancer, bladder cancer, and gastric cancer. Nevertheless, the specific function of MAFG-DT in the context of bone metastasis in PCa remains inadequately understood.MethodsThe expression level of MAFG-DT was analyzed in published datasets and further confirmed in clinical samples and cell lines by RT-qPCR and in situ hybridization assays. Additionally, we further examined the effect of MAFG-DT on cell proliferation, migration, invasion and bone metastasis through CCK8, EdU, colony formation, transwell assays and bone metastasis model with intracardiac injection. Subsequently, the specific mechanism of MAFG-DT in PCa was investigated by RIP, ChIP, bioinformatic analysis and luciferase reporter assays.ResultsWe found that MAFG-DT expression was significantly upregulated in PCa tissues exhibiting bone metastasis. Elevated levels of MAFG-DT expression were found to be positively associated with poor prognostic outcomes in PCa patients. Functionally, the knockdown of MAFG-DT resulted in a pronounced inhibition of cellular proliferation, migration, invasion, and bone metastasis. Moreover, it was demonstrated that MAFG-DT enhanced the expression of FZD4 and FZD5 mRNAs by sequestering miR-24-3p, thereby activating the Wnt/β-catenin signaling pathway. Additionally, the transcription factor MAFG was found to transcriptionally activate MAFG-DT in PCa.ConclusionThis study confirms the oncogenic role of MAFG/MAFG-DT/miR-24-3p/Wnt/β-catenin in PCa, which suggests that MAFG-DT could serve as a potential therapeutic target for PCa.